Case report: Thyroid storm in a three-year-old girl presenting with febrile status epilepticus and hypoglycemia - Aoki, Yusuke; Hanaki, Ryo; Toyoda, Hidemi; Emori, Koichi; Miyahara, Masazumi; Hirayama, Masahiro (Frontiers in Pediatrics, 2023)
Thyroid storm, though extremely rare in toddlers, requires prompt diagnosis and treatment because it can be fatal if left untreated. However, thyroid storm is not often considered in the differential diagnosis of a febrile convulsion due to its rarity in children. Herein, we report the case of a 3-year-old girl with thyroid storm who presented with febrile status epilepticus. Although the seizure was stopped by diazepam administration, her tachycardia and widened pulse pressure persisted, and severe hypoglycemia was observed. Based on the findings of thyromegaly, a history of excessive sweating and hyperactivity, and a family history of Graves' disease, she was eventually diagnosed with a thyroid storm. The patient was successfully treated with thiamazole, landiolol, hydrocortisone, and potassium iodide. Propranolol, a non-selective β-blocker, has been used to manage tachycardia during thyroid storm. However, a cardio-selective β1-blockers, landiolol hydrochloride, was used in our case to avoid worsening hypoglycemia. Febrile status epilepticus is one of the most common medical emergencies in childhood; it is necessary to rule out treatable underlying critical diseases such as septic meningitis and encephalitis. Thyroid storm should be considered in children presenting with prolonged febrile convulsion accompanied by findings that are not usually observed with febrile convulsions.